Studies toward the Total Synthesis of Sorangicins: A Shortened Synthesis of the Dioxabicyclo[3.2.1]octane Core - Michaelis, Lars; Schinzer, Dieter (Synlett, 2014)
An access to the dioxabicyclo[3.2.1]octane core of sorangicin A was developed, using a keto lactone formation, a Mukaiyama–Michael reaction and an epoxide opening as the key steps.
Keywords: sorangicin A; antibiotic activity; asymmetric synthesis; dioxabicyclo[3.2.1]octane core; Mukaiyama–Michael reaction